THE GENERATION AND SHAPE OF FEEDER DYKES FROM MANTLE SOURCES - Maaløe S. (My University, 1987)
The criterion for fracture propagation suggests that the primary magma generated in the mantle ascends in a stepwise fashion. Initially a pulse of magma forms a dyke above the mantle source and ascends for some distance, whereafter it stops. A subsequent pulse of magma joins the first one, and the ascent of the accumulating body of magma continues for some distance each time a new pulse of magma reaches the body of magma situated in the top of the dyke. In this manner a dyke is formed that may extend either partly or the whole way from the mantle source to the surface. This model may explain the large pressures, up to 2000 bars, that prevail during basaltic eruptions. The calculated shape of the ascending pulses of magma suggests that their heights and widths are similar.